Changes in hemolymph characteristics of ark shell Scapharaca broughtonii dealt with Vibrio anguillarum challenge in vivo and various of anticoagulants in vitro. Issue 61 (February 2017) - Zhou, Liqing; Yang, Aiguo; Liu, Zhihong; Wu, Biao; Sun, Xiujun; Lv, Zhenming; Tian, Ji-teng; Du, Meirong
Abstract: The ark shell Scapharca broughtonii is a commercially important shellfish in China. Alserver's solution (AS), modified Alserver's solution (MAS) and Heparin sodium solution (HSS) are common anticoagulants used for shellfish blood. To observe the immune response mediated by its hemocytes, we challenged in vivo S. broughtonii hemolymph with Vibrio anguillarum and dealt with the following three anticoagulants in vitro : Alserver's solution (AS), modified Alserver's solution (MAS) and Heparin sodium solution (HSS). The methodologies we used were immunostimulation with V. anguillarum, Wright-Giemsa staining, micro-examination, and flow cytometric and hydrolyzing enzyme activity analysis. The results showed that all three types of anticoagulants effectively prevented blood clotting in ark shellfish. The morphology of hemocytes did not significantly change 30 h after anticoagulant treatment, except for the shrinking of hemocytes after administering HSS. The size and permeability of hemocytes changed when treated with the anticoagulants and when stimulated with V. anguillarum . Both alkaline phosphatase (AKP) and acid phosphatase (ACP) in hemocytes and Plasma were measured at different times after they were stimulated with V. anguillarum in HSS and MAS. The AKP enzymatic activity in HSS was somewhat higher than in the MAS anticoagulant, but changes in response to V. anguillarum challenge of enzymatic activity were almost the same in HSS and MAS groups. In conclusion, all three types of anticoagulants may be used for ark shell blood preservation. They all changed the cell-surface characteristics of hemocytes to inhibit clot formation. The AS anticoagulant was appropriate for maintaining white and red cell shapes, while MAS was ideal for retaining throbus cell function. Lastly, HSS was appropriate for maintaining enzymatic activity in hemolymph and function of hemocytes. Following this investigation, we gained insight into the changes in hemolymph characteristic during immune response. Highlights: We studied Changes in hemolymph characteristics of shellfish hemolymph challenged with Vibrio anguillarum under various anticoagulants. All three types of anticoagulants may be used for ark shell blood preservation. The size and permeability of hemocytes changed when treated with the anticoagulants. Thrombus cells of S. brouthtonii may change in various anticoagulants solutions.